Correlation of skin rash and overall survival in patients with pancreatic cancer treated with gemcitabine and erlotinib-results from a non-interventional multi-center study - Westphalen, C. Benedikt; Kukiolka, Tobias; Garlipp, Benjamin; Hahn, Lars; Fuchs, Martin; Malfertheiner, Peter; Reiser, Marcel; Kütting, Fabian; Heinemann, Volker; Beringer, Andreas; Waldschmidt, Dirk T. (BMC Cancer, 2020)
Background: Gemcitabine/erlotinib treatment offers limited benefit in unselected patients with pancreatic ductal adenocarcinoma (PDAC). Development of skin rash has been associated with favorable outcomes in patients treated with gemcitabine/erlotinib. This study aimed to extend knowledge on the effectiveness of gemcitabine/erlotinib in metastatic PDAC in the context of clinical practice and with focus on skin rash. Methods: This multicenter, non-interventional study enrolled 376 patients with metastatic PDAC receiving gemcitabine/erlotinib. The primary endpoint was overall survival (OS) in patients with skin rash versus no skin rash. Secondary endpoints included progression-free survival (PFS), treatment satisfaction and safety. All data were analyzed using descriptive statistics. Survival time and time to disease progression were estimated using the Kaplan-Meier method. Effectiveness endpoints were analyzed for subgroups by skin rash grade (no rash, rash grade 1, rash grade ≥ 2), duration of erlotinib treatment (≤8 weeks, > 8 weeks), Eastern Cooperative Oncology Group (ECOG) performance status at baseline (0-1, 2) and age (≤65 years, > 65 years). Results: Within the full analysis set (FAS; N = 270), 48 patients (17.8%) developed grade 1 rash, 51 patients (18.9%) grade ≥ 2 rash, while 171 patients (63.3%) did not develop a rash. Median OS of all patients was 9.11 months with an OS of 9.93 months in rash-positive and 8.68 months in rash-negative patients. Median PFS was 5.06 months for rash-positive and 4.11 months for rash-negative patients. PFS was longer in patients with rash grade ≥ 2 and in older patients (> 65 years). Examination using a multivariate Cox proportional model revealed that an age > 65 years was associated with longer OS (hazard ratio 0.640; p = 0.0327) and PFS (hazard ratio 0.642; p = 0.0026). Out of the 338 patients in the SAF, 310 patients (91.7%) experienced at least one AE, and 176 patients (52.1%) experienced skin-related side effects, all of which were CTC grade 1 to 3. Conclusions: Comparing rash-positive with rash-negative patients showed no significant difference in survival. While patients with rash grade ≥ 2 and older patients (independent of skin reactions) showed longer PFS, this did not translate into prolonged OS. The study did not reveal new safety signals. Trial registration: ClinicalTrials.gov Identifier: NCT01782690, retrospectively registered on 4 February 2013.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Erlotinib; Gemcitabine; Non-interventional study; Overall survival; Pancreatic ductal adenocarcinoma; Progression-free survival; Skin rash